Effects of plyometrics and plyometrics combined with dynamic stretching on vertical jump in male collegiate volleyball players - Usman, T.; Shenoy, K. B. (International Journal of Applied Exercise Physiology, 2019)
Vertical jump ability is a crucial component for success in volleyball. Plyometric training is used to generate and enhance explosive power of athletes in various sport activities. The aim of this study was to find out the comparative effects of lower body plyometric exercises and lower body Plyometrics combined with dynamic stretching on vertical jump performance in male collegiate volleyball players. The study was conducted for an eight weeks period on 90 male collegiate volleyball players of 18-22 years of age. Players were divided randomly into one control and two experimental groups of 30 players in each group. All players were tested for vertical jump height using the sergeant jump test prior to start of the training program. The assessments were done at the end of every two weeks till eight weeks. The results of the study show that significant changes in vertical jump height from 2nd week onwards in both the groups and the highest effects were observed at the end of 8 Weeks(p<0.05). However, the lower body plyometrics combined with dynamic stretching group showed more effect than the lower body plyometrics group. It can be concluded that eight week lower body plyometrics combined with dynamic stretching training can be the better effective technique to improve vertical jump performance in male collegiate volleyball players.